Working Capital Turnover Analysis of Profitability Levels at PT Semen Indonesia (Persero) Tbk - Nurul Amanda; Romansyah Sahabuddin; Nurman (Economics and Business Journal (ECBIS), 2023)
This study aims to determine the effect of working capital turnover (WCTO) on the level of profitability (ROA) at PT Semen Indonesia (Persero) Tbk. The population in this study is all financial report data of PT. Semen Indonesia (Persero) Tbk for the 2013-2020 period, while the samples in this study are statements of financial position and profit/loss statements. The documentation technique is the data collection technique used. The data collected was analyzed using financial ratios, simple regression analysis, correlation coefficients and t-test with the SPSS (Statistic Product and Service Solution) 24 For Windows program. The findings in this study show that working capital turnover (WCTO) and profitability (ROA) have increased quarterly every year as measured by financial ratios. The results of the t-test show that the working capital turnover variable (WCTO) has a positive and significant influence on the level of profitability. The hypothesis in this study is accepted.